A framework for innovation decision making in the internet age. (23rd November 2005) - Lan, Ping
This paper aims to advance our understanding of innovation decision making among organisations in the Internet Age. By identifying an asymmetry existing between outward driving forces and inward shaping forces of innovation, it develops a framework for integrating the two driving forces and supporting innovation decision making in the changing world. By means of incorporating the changes of innovation environment, innovation practices and innovation paradigm, the framework provides us with a useful tool for dealing with innovation issues in a networked business environment.